Immunogenicity of BNT162b2 Vaccine Booster Dose in Patients With Inflammatory Bowel Disease Receiving Infliximab Combination Therapy: A Prospective Observational Study - Shehab, Mohammad; Alrashed, Fatema; Alfadhli, Ahmad; Alsayegh, Abdulwahab; Aldallal, Usama; Alsayegh, Mariam; Cherian, Preethi; Alkhair, Irina; Thanaraj, Thangavel Alphonse; Channanath, Arshad; Dashti, Ali A.; Albanaw, Anwar; et al. (Frontiers in Medicine, 2022)
Introduction: Few data exist regarding the immunogenicity of third dose of BNT162b2 relative to second dose in patients with inflammatory bowel disease (IBD) on different immunosuppressive therapies. We investigated the immunogenicity of BNT162b2 vaccine booster dose in patients with IBD on infliximab combination therapy. Methods: This is prospective single center observational study conducted between January 1st, 2022 until February 28th, 2022. Patients were recruited at the time of attendance at the infusion center. Eligibility criteria included patients with confirmed diagnosis of IBD who are receiving infliximab with azathioprine or 6-mercaptopurine and have received two or three-dose of BNT162b2 vaccine. Patients were excluded if they were infected or had symptoms of SARS-CoV-2 previously since the start of the pandemic or received other vaccines than the BNT162b2. Our primary outcome was the concentrations of SARS-CoV-2 antibodies Immunoglobulin G (IgG) and neutralizing antibodies 40-45 weeks from the first dose of BNT162b2 in patients with IBD receiving infliximab combination therapy. Medians with interquartile range (IQR) were calculated. Results: 162 patients with IBD and receiving infliximab combination therapy were recruited and the number of patients in each group was 81. Median (IQR) SARS-CoV-2 IgG levels were significantly lower after the second dose [125 BAU/mL (43, 192)] compared to patients who received the third booster dose [207 BAU/mL (181, 234)] (p = 0.003). Neutralizing antibody levels were also lower after the second dose [80 BAU/mL (21, 95)] compared to patients who received the third booster dose [96 BAU/mL (93, 99)] (p = <0.001). The percentage of patients who achieved positive SARS-CoV-2 IgG levels in the third (booster) dose group was higher (96.3%) than those in second dose group (90%)(p = 0.026). Percentage of patients who received third (booster) dose and achieved positive SARS-CoV-2-neutralizing antibody level was 100%, whereas it was lower (88.9%) in patients who received second dose only (p=0.009). Conclusion: Most patients with IBD on infliximab combination therapy had positive SARS-CoV-2 IgG and neutralizing antibody concentrations 40-45 weeks post BNT162b2 vaccination. However, SARS-CoV-2 IgG and neutralizing antibody concentrations were lower in patients who received 2 doses only compared to patients who received a third dose.